Symptomatic Images/Contagious Images: The Ambivalence of Visual Narratives of Eating Disorders (Cinéma & Cie. Film and Media Studies Journal, 2023)
The connection between images and anorexia, orthorexia, bulimia, binge eating, and other forms of food consumption deemed ‘disordered’ is controversial and often over-simplified. Frequently it is reduced to the idea that glamorous images, particularly the heroin chic style of the 1990s, create a dangerous imaginary that young women - statistically the main target of eating disorders - emulate. This article wants to challenge this issue by exploring three aspects of the intricate relationship between eating disorders and images: 1) The fear of contagion that haunts images exposing bodies that suffer by eating disorders; 2) As a time-based medium, film offers a privileged set of perceptive tools to account for the ways eating disorders interfere with time – as perceived, lived, shared; 3) One more aspect that is relevant to observe since it predominately occupies the current debate is the question of the right way to represent certain medical conditions and their experience. The reasons at the core of this debate are extremely vital and prove how photos and moving images have tragically contributed to building and constructing gender and racial bias as well as the stigmatization of certain diseases. Though when speaking of misrepresentation there is the risk of embracing a deceptive idea of good mimesis at the cost of the ambivalence that the experience of certain conditions inherently carry and which should not disappear in the fictional dimension.
Keywords: Anorexia; Bulimia; Moara Passoni; Dysmorphia; Film